Covering Politics in the Age of Trump - Ceppos, Jerry (Book collections on Project MUSE., 2021)
"Like politics, journalism has been turned topsy-turvy by the presidency of Donald Trump. "Covering Politics in the Age of Trump" takes a wide-ranging view of the relationship between the forty-fifth president and the Fourth Estate. In concise, illuminating, and often personal essays, twenty-four top journalists address topics such as growing concerns about political bias and journalistic objectivity; increasing consternation about the media's use of anonymous sources; the practices journalists employ to gain access to wary administration officials; and reporters' efforts to improve journalism in an era of twenty-four-hour cable news. Contributors include: Major Garrett of CBS News; Mark Leibovich, best-selling author and chief national correspondent for the New York Times Magazine; Paul Farhi, media writer for the Washington Post; Rebecca Buck, a campaign reporter for CNN; Charlie Cook of the Cook Political Report; and Steve Thomma, executive director of the White House Correspondents' Association; among many others. The Trump administration's contentious relationship with the media has altered the public's expectations regarding the news and national politics. In "Covering Politics in the Age of Trump," top political reporters explore this dynamic, relaying stories from the campaign trail to the briefing room that illustrate the new challenges faced by journalists working in the age of "fake news.""--